Predictive value of the induction test with atrial burst pacing with regard to long‐term recurrence after ablation in persistent atrial fibrillation. Issue 2 (18th January 2019) - Kawai, Shunsuke; Mukai, Yasushi; Inoue, Shujiro; Yakabe, Daisuke; Nagaoka, Kazuhiro; Sakamoto, Kazuo; Takase, Susumu; Chishaki, Akiko; Tsutsui, Hiroyuki
Abstract: Background: Induction test of atrial fibrillation (AF) is one of endpoint measures in catheter ablation (CA). However, its predictive value in long‐term outcome remains controversial. Methods: Ninety‐eight patients (61 years, 77 males) with persistent AF who underwent pulmonary vein antrum isolation‐based CA were retrospectively analyzed. We determined whether inducibility of AF/atrial tachyarrhythmias (AT) by atrial burst pacing at the end of CA and other characteristics were associated with the recurrence of AF/AT. Atrial burst pacing was performed with 30‐beat from the coronary sinus; increasing from 240 to 320 ppm. Inducibility was defined as AF/AT lasting ≥5 minutes following atrial burst pacing. Results: AF/AT was induced in 50 patients (51%). During 1 year of follow‐up, 71 patients (72.4%) had no recurrence of AF/AT. A logistic regression analysis showed that female gender (OR 3.8; P  = 0.02), multiple sessions (OR 3.5; P  = 0.02), and early recurrence of AF/AT (OR 5.3; P  = 0.004) were associated with clinical recurrence. AF/AT Inducibility was not associated with clinical recurrence ( P  = 0.65). A subanalysis in patients with enlarged LA (LA diameter ≥45 mm, n = 40) showed that AF/AT inducibility was associated with recurrence (OR 8.1; P  = 0.04). The positive and negative predictive values of AF/AT inducibility for AF/AT recurrence were 41 and 89%, respectively. Negative predictive value was increased to 92.3% when the inducibility was defined as AF/AT of ≥30 seconds following atrial burst pacing. Conclusions: AF/AT inducibility cannot predict long‐term clinical recurrence in patients with persistent AF. However, it may have a prognostic value especially in patients with enlarged LA.